Effect on mode of Child birth and its outcomes before and during the COVID-19 pandemic at Ilam district hospital: A comparative descriptive cross-sectional study - Sah, Prabhu; Shrestha, Shradha; Deo, Anju; Karn, Shivam (Birat Journal of Health Sciences, 2022)
Introduction: Nepal started full lockdown from 24 March to 14 June 2020, followed by partial lockdowns multiple times as a precaution for the prevention of COVID-19 infection. Managing health care services was a major issue during the COVID-19 pandemic for both the patients and health care professionals including services targeting pregnant women in developing countries like Nepal. Objectives: To study the impact of the COVID-19 pandemic on childbirth services attended at a district government hospital and to observe the impact on mode of delivery and maternal-child health. Methodology: This descriptive cross-sectional study aimed to find out the impact on delivery services during the pandemic compared to pre-pandemic duration that includes one year period from 22nd October 2019 to 22nd March 2020 (before pandemic) and from 23rd March 2020 to 23rd September 2020 (pandemic duration) at Ilam District Hospital. All the information used in this research was taken from Health Management Information System (HMIS) logbook. The permission to use the recorded data was obtained from the hospital. Anonymity and confidentiality of data were maintained and no personal information was used in this research to protect the identity of the patients. The data was collected from the HMIS records of the hospital and was then processed in Microsoft excel. Results: The result shows despite the lockdown and pandemic the percentage of patients coming to receive delivery services within the hospital increased about 9% which is an exceptionally good result. Emergency CS was found to be decreased by 3%. During the pandemic Hospital stay was significantly reduced for patient’s safety due to COVID-19. However, no adverse impact was observed on the health outcomes of the mother and baby due to a short stay at the hospital. Conclusion: Despite lockdown and pandemic, the number of parents receiving hospital delivery services increased at Ilam hospital. This was possible due to proper management and pre-plan services according to the government’s COVID-19 protocol to cope with the pandemic and demand of the health services as other nearby hospitals closed their door during the pandemic. In the future, a short stay at the hospital can be continued to cope with a high demand of the services in the maternity department as we found the health of both mother and baby has not been impacted due to short stay in the hospital during the pandemic.